2007
DOI: 10.1002/ptr.2067
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo antimalarial activity of aqueous extracts from Kenyan medicinal plants and their Chloroquine (CQ) potentiation effects against a blood‐induced CQ‐resistant rodent parasite in mice

Abstract: Hot water extracts from eight medicinal plants representing five families, used for malaria treatment in Kenya were screened for their in vivo antimalarial activity in mice against a chloroquine (CQ) resistant Plasmodium berghei NK65, either alone or in combination with CQ. Extracts of three plants, Toddalia asiatica (root bark), Rhamnus prinoides (leaves and root bark) and Vernonia lasiopus (root bark) showed high chemosuppression in the range 51%-75%. Maytenus acuminata, M. heterophylla, M. senegalensis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 21 publications
(21 reference statements)
2
25
0
Order By: Relevance
“…The difference between the antimalarial activities of extracts of both plants in all the three solvents may indicate differences in the level and composition of active compounds [29]. The difference may also be due to differences between the solvents used for the extraction of the plant materials as the secondary metabolites/compounds could be different.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the antimalarial activities of extracts of both plants in all the three solvents may indicate differences in the level and composition of active compounds [29]. The difference may also be due to differences between the solvents used for the extraction of the plant materials as the secondary metabolites/compounds could be different.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need for innovative and alternative strategies to combat the resistant strains of the parasite. Some studies have shown that plant-based preparations, co-administered with orthodox drugs, produced better antimalarial activities on both chloroquine (CQ)-sensitive and CQ-resistant Plasmodium strains (Ahorlu et al 1997;Muregi et al 2003Muregi et al , 2007Adibe 2009;Anagu et al 2014). MAMA decoction (MD), an herbal remedy prepared from a mixture of the leaves of Mangifera indica L. (Anacardiaceae), Alstonia boonei De Wild (Apocynaceae), Morinda lucida Benth (Rubiaceae) and Azadirachta indica A. Juss (Meliaceae) in equal proportions, has been reported to possess antimalarial activities on CQ-sensitive P. berghei NK65 in rodents with acceptable safety (Akanmu et al 2013;Adepiti et al 2014;Odediran et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…M. heterophylla and M. senegalensis are used to treat respiratory ailments and inflammation (da Silva et al, 2011). The in vivo antiplasmodial (Muregi et al, 2007) and in vitro antileishmanial activities (Matu and van Staden, 2003) of different species of the genus Maytenus have been reported previously. Antimicrobial activities of various Maytenus ssp.…”
Section: Introductionmentioning
confidence: 91%